Material testing and results estimation by safety indexes - Mykyichuk, Mykola; Rudyk, Yuriy (Видавництво Львівської політехніки, 2021)
In the article, both the test method features and the test results of research of thermal behavior of steel fragment were analyzed. Two types of test conditions for steel construction material were considered. The definition and main features of measurement techniques were presented. Fire retardant material test results for steel plates with hydrogen combustion shown the limit of fire resistance of the tested samples is more than 30 min. The main advantages and disadvantages of the test were determined. The positive and negative aspects of this approach were analyzed. These techniques' effective thermal condition is in an environment of uncertainty and has no limited resources was established. Concepts and principles for establishing validity, and frameworks and methods for validating test methods and their results are important elements of safety systems. The article considers the safety of the technical component of a complex organizational and technical system with the study of the functional relationship between the safety elements parameters: temperature, time, fire retardant – by hydrogen participation.
Keywords: Validation; Hydrogen fire temperature; Measurement method; Quality control; Metrological support